Assessment Trends in Science Learning in Junior High School: A Systematic Review - Syafira, Annisa; kurniawati, Yenni; Siagian, Liza Maulida; Putra, Niki Dian Permana (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2025)
Effective assessment practices are essential in improving science education, yet determining the most suitable types of assessment for junior high school science remains a challenge. Current assessment practices often focus heavily on cognitive outcomes, with less emphasis on evaluating students’ scientific process skills and attitudes. This study aims to identify and analyze the most effective assessment methods used in junior high school science education over the past decade. A systematic review method was employed to collect and examine relevant peer-reviewed articles published between 2014 and 2024. The review reveals a growing trend in the use of authentic assessment, which includes performance tasks, project-based learning assessments, and portfolios. Authentic assessment is identified as the most effective approach, as it holistically evaluates students’ knowledge, skills, and attitudes in realistic contexts, aligning with the objectives of the national curriculum. The findings suggest that educators and policymakers should prioritize the development and implementation of authentic assessments to foster deeper learning and better prepare students for real-world problem-solving.